Application of the Learning Contract Learning Method to History Learning Activities of Class X Students in Online Business and Marketing at State Vocational High School 1 Pontianak - Lidia, Lidia; Ulfa, Maria; Putri, Astrini Eka (JURNAL HISTORICA, 2023)
This research was conducted with the aim of knowing the application of the learning contract learning method to the learning activities of class X BDP students at Vocational High School 1 Pontianak. This research is a quantitative research with experimental method. The data source was used by students of class X BDP 1 as the experimental class and class X BDP 2 as the control class. Data collection through questionnaires and documentation. From the results of the research the researchers found that: The implementation of learning history using the learning contract learning method includes planning by determining learning objectives, applying learning contract learning methods and evaluating. Student activities during the learning process showed that students were able to explain material about the origins of their ancestors and conduct group discussions. In the learning process using the learning contract learning method there is an influence on the history learning activities of class X BDP SMK Negeri 1 Pontianak. As for learning activities such as arriving on time, listening to subject matter and having group discussions related to historical material. In this case the learning contract learning method aims to achieve what is planned as well as possible. Keywords: Learning Menthods, Learning Contract, Activity